The asymptotical expansions for the density of the sum of multidimensional random variables combined into nonhomogeneous Markov chain - Lapinskas, R. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Лапинскас. Асимптотические разложения для плотности суммы многомерных случайных величин, связанных в неоднородную цепь Маркова R. Lapinskas. Apie daugiamačių atsitiktinių dydžių, surištų į nehomogeninę Markovo grandinę, sumos tankio asimptotinius dėstinius